(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Wireless mobile computing is type of computation by which various mobile gadgets gives services to us at numerous ways. In wireless computing of mobile one can find the working of sensors ad hoc networks odysseys and rover etc. Not only has this wireless based mobile computing service also suggested that a user can take the services of networks any time anywhere without any disturbances[1]. This includes the physical location time place authentication etc. which paves way for making mobile services successful. The research paper also describes about merits and disadvantages of wireless mobile computing along with many challenges faced by it in remote areas. Additionally, this paper also states how we get adapted to the ecosystem of wireless network from the long process of wired networks. Mobile agent is one of the most important elements in computing. It is clearly described in this research paper. This research paper also throws ample amount of light on the working of sensors and its unique features[12]. Wireless computing makes our life totally comfortable by its outstanding services. Here all useful services of that are clearly mentioned. At last the conducting of wireless mobile computing in all areas of the world is much more important for the welfare of future generations [9]. This research paper describes about the steps with measures needed in implementing wireless computing everywhere.